Ultramicronized palmitoylethanolamide reduces viscerovisceral hyperalgesia in a rat model of endometriosis plus ureteral calculosis: role of mast cells. Issue 1 (January 2016) - Iuvone, Teresa; Affaitati, Giannapia; De Filippis, Daniele; Lopopolo, Mariangela; Grassia, Gianluca; Lapenna, Domenico; Negro, Luana; Costantini, Raffaele; Vaia, Massimo; Cipollone, Francesco; Ialenti, Armando; Giamberardino, Maria Adele
Abstract : Abstract: The effects of ultramicronized palmitoylethanolamide were evaluated on pain behaviours and markers of mast cell (MC) activity in a rat model of endometriosis plus ureteral calculosis (ENDO+STONE)–induced viscerovisceral hyperalgesia (VVH). Female Sprague-Dawley rats that underwent surgical induction of endometriosis were randomly assigned to receive active (ultramicronized palmitoylethanolamide 10 mg·kg −1 ·d −1, orally) or placebo treatment for 25 days. At day 21, they underwent ureteral stone formation and were video-recorded till day 25 to evaluate ureteral and uterine pain behaviours. At autopsy (day 25), ureteral condition and number and diameter of endometrial cysts were evaluated. The following were then measured: number and percentage of degranulating MCs, number of vessels, chymase, nerve growth factor (NGF), vascular endothelial growth factor (VEGF), and Flk-1 (VEGF receptor) in cysts, and NGF in dorsal root ganglia (DRG). Ultramicronized palmitoylethanolamide–treated vs placebo-treated rats showed significantly lower number, duration and complexity of ureteral crises, shorter duration of uterine pain, and smaller cyst diameter (0.0001 < P < 0.004); a significantly higher percentage of expelled stones ( P < 0.0001); significantly lower MC number ( P < 0.01), vessel number ( P < 0.01), chymase ( P < 0.05), NGF ( P < 0.05), VEGF ( P < 0.01), and Flk-1 ( P < 0.01) expression in cysts and NGF expression in DRG ( P < 0.01). In all animals, the global duration of ureteral crises correlated linearly and directly with cyst diameter, MC number and chymase in cysts, and NGF in cysts and DRG (0.02 < P < 0.0002). Ultramicronized palmitoylethanolamide significantly reduces VVH from ENDO+STONE, probably by modulating MC expression/activity in cysts, thus reducing central sensitization due to noxious signals from endometriotic lesions. The results suggest potential utility of the compound for VVH in clinics. Abstract : In rats with endometriosis plus ureteral calculosis, oral ultramicronized palmitoylethanolamide vs placebo significantly reduces viscerovisceral hyperalgesia by downregulating mast cell activity in endometriotic lesions.